How do different treatment modalities impact long-term remission rates and fertility preservation in patients with gestational trophoblastic diseases? : A Systematic Review - Sharly Ayu Puspita; Dini Gustiarini (International Medical Journal Corp. Ltd, 2025)
Introduction: The management of Gestational Trophoblastic Disease (GTD) aims to achieve high long-term remission rates while preserving future fertility. Treatment protocols are stratified by risk to optimize outcomes and minimize toxicity. This systematic review synthesizes current evidence on how different treatment modalities impact remission and fertility in GTD patients. Methods: This systematic review adhered to PRISMA 2020 guidelines. Databases including PubMed, Semantic Scholar, Springer, and Google Scholar were searched using PICO-based keywords to identify relevant studies. After screening, 25 studies—including randomized controlled trials, cohort studies, and systematic reviews—were selected for data extraction and analysis on treatment protocols, remission rates, and fertility outcomes. Results: For low-risk Gestational Trophoblastic Neoplasia (GTN), single-agent chemotherapy (methotrexate or actinomycin D) achieves remission rates of 75-100%. For high-risk GTN, multi-agent regimens like EMA/CO result in remission rates between 71% and 97.7%. Immunotherapy with avelumab has shown approximately a 53% remission rate in chemo-resistant cases. Fertility preservation is a significant success, with subsequent pregnancy rates of 86.7-100% and live birth rates of 75.8-90% reported after chemotherapy. Surgical interventions such as routine second uterine curettage or hysterectomy did not demonstrate improved remission rates over chemotherapy alone. Discussion: The evidence strongly supports a risk-stratified treatment model that balances efficacy with toxicity. The choice between single agents like methotrexate and actinomycin D depends on their differing toxicity profiles. The emergence of immunotherapy has provided a crucial and effective option for patients with chemo-resistant disease, transforming the prognosis for this group. Conclusion: The treatment of GTD is highly effective, yielding excellent remission rates while safeguarding patient fertility. The standard of care relies on risk-stratified chemotherapy, with effective, evidence-based salvage therapies like immunotherapy available for resistant disease. These modern strategies ensure high cure rates and preserve quality of life, including future reproductive potential.